KEWENANGAN PENERBITAN SERTIFIKASI PROFESI ADVOKAT OLEH ORGANISASI ADVOKAT (STUDI PUTUSAN MAHKAMAH KONSTITUSI No. 35/PUU-XVI/2018) - Septino Guntur Pamungkas; Rusdianto Sesung; Zawida Ainia (Jurnal HUKUM BISNIS, 2023)
The establishment of the Bar Association by Act No. 18 of 2003 on Lawyers has raised a debate as to which organization is recognized by the law. The decision of the Constitutional Court No. 35/Law-XVI/2018 on the Organization of Lawyers is the result of the material examination request submitted by a number of lawyers. The research method used is Normative research. The results of the research indicate that Peradi is the only container of the lawyer profession has eight authorities. The existence of advocacy organizations outside the existing Peradi cannot be prohibited as an expression of freedom of association and assembly guaranteed by Article 28 and Article 28E paragraph (3) of the 1945 UUD. Only, the lawyer's organization is not authorized to exercise those eight powers as contained in the MK Decision No. 66/Law-VIII/2010 dated 27 June 2011. Therefore, any action by a lawyer's organization other than PERADI that appears to be exercising one of the eight (eight) powers of PERADI granted by the Law on Lawyers is an act against the law that is detrimental to PERADI as the sole party entitled to such authority. Keywords: lawyers, advocates, lawyer organizations